Determinants for creation and addition of value to the coffee in Dosquebradas municipality (Risaralda, Colombia) (2019)
This article proposes to answer the question, ¿why Colombia, as well RisaraldaDepartment has not progressed in the coffee-value-chain historically?. It alsomakes an exploratory review of the current state at the coffee market in theworld and a field work to identify what is being done in Dosquebradas city tobetter the competitive conditions for coffee cultivation through partnershipsand introduce the culture of specialty coffees